PERENCANAAN DAN PENGADAAN OBAT DI PUSKESMAS SURABAYA TIMUR DAN SELATAN - Athijah, Umi; Zairina, Elida; Sukorini, Anila Impian; Rosita, Efrita Mega; Putri, Anindita Pratama (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
Primary Health Center as an organization of public health service has an excellent service quality character, besides qualified medical services. Service will run if the availability and quality of medicines is assured. This study was conducted to get an overview of planning and procurement of medicines at primary health centers. It was observational and descriptive study. The sample was the entire primary health centers in South and East Surabaya (n = 26) and the respondent was the staff of primary health center who manage planning and procurement of medicines. The data was collected by validated questionnaires and check list. Results showed that 57.7% respondents was pharmacists. Non-DOEN generic medicines and patent medicines were provided by 61.5%. The combined method (epidemiology-consumption method) was used by 61.5% staff to calculate the medicine need. The unschedule procurements have been reported by 57.7% respondents. "Received medicine was not always the same with the request" was reported by 69.2% staff. Only 19.2% respondents always check the medicine name, strength, quantity, dosage form, expired date, batch number and physical condition. To conclude, the medicine demand has not been well covered and only a few staff always check the medicines completely. ABSTRAK Penelitian ini dilakukan untuk mendapatkan gambaran tentang perencanaan dan pengadaan obat di puskesmas. Sampel adalah seluruh puskesmas di wilayah Surabaya Selatan dan Timur (n=26) dengan responden yaitu pengelola obat di setiap puskesmas. Pengambilan data menggunakan kuesioner dan check list yang telah divalidasi. Dari penelitian ini diketahui bahwa 57,7% pengelola obat di puskesmas adalah apoteker. Sebanyak 61,5% menyediakan obat generik non-DOEN dan obat paten selain obat generik DOEN yang dipersyaratkan. Metode campuran konsumsi dan epidemiologi digunakan oleh 61,5% pengelola dalam menghitung kebutuhan obat. Permintaan obat di luar jadwal pernah diajukan oleh 57,7% responden. “Penerimaan obat tidak selalu sama dengan permintaan” dilaporkan oleh 69,2% pengelola, namun hasil pengamatan dalam checklist menunjukkan seluruh puskesmas mengalami hal tersebut. Hanya 19,2% responden melakukan pengecekan nama obat, kekuatan, jumlah, bentuk sediaan, tanggal kadaluarsa, nomor lot dan kerusakan obat. Kesimpulan yang diperoleh adalah kebutuhan obat di puskesmas masih belum terpenuhi dengan baik terutama karena faktor pengadaan dan hanya sebagian kecil pengelola obat yang melakukan pengecekan obat secara lengkap.